2009
DOI: 10.1016/j.jhazmat.2009.01.130
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic treatment of 4-chlorophenol in aqueous ZnO suspensions: Intermediates, influence of dosage and inorganic anions

Abstract: The photocatalytically driven removal of eco-persistent 4-chlorophenol from water using ZnO is reported here. Kinetic dependence of transformation rate on operating variables such as initial 4-chlorophenol concentration and photocatalyst doses was investigated. A complete degradation of 4-chlorophenol at 50 mg L(-1) levels was realised in 3h. Analytical profiles on 4-chlorophenol transformation were consistent with the best-line fit of the pseudo zero-order kinetics. The addition of small amounts of inorganic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(84 citation statements)
references
References 40 publications
7
74
0
2
Order By: Relevance
“…As a result, in recent years continuous efforts have been made to develop innovative technologies in order to remediate polluted environment. Among them, photocatalysis serves as an attractive tool due to its efficiency and relatively low cost [4]. Currently the most widely used and studied photocatalyst is titanium dioxide (TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, in recent years continuous efforts have been made to develop innovative technologies in order to remediate polluted environment. Among them, photocatalysis serves as an attractive tool due to its efficiency and relatively low cost [4]. Currently the most widely used and studied photocatalyst is titanium dioxide (TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Air was bubbled from the lower part of the apparatus by a specular draft tube hung vertically from the top of the reactor. Other features of the reactor have been described previously (Gaya et al, 2009). The apparatus was maintained at controlled temperature of 299 K by circulating water in and out of the outer jacket.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Similarly, in photodefluoridation of pentafluorobenzoic acid, the reaction rate was reduced by both HPO 4 2-and SO 4 2-and accordingly, the former demonstrated the highest inhibition (Ravichandran et al, 2007). The mechanism of rate inhibition by HPO 4 2-has not been clear but the blockage of the active sites of the semiconductor particles has recently been suggested (Gaya et al, 2009). The reduction in removal rate in presence of Cl -and SO 4 2-has been attributed to the scavenging of hydroxyl radical by these anions as shown in Eq.…”
Section: Effect Of Anion Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last three decades, heterogeneous photocatalytic oxidation processes with TiO 2 -based materials and binary oxides have been investigated for the remediation of water resources contaminated by recalcitrant hydrocarbons [1][2][3][4][5][6][7][8][9][10][11]. These studies have reported that highly reactive transitory species (e.g., superoxide radical (O 2 · − ), hydroxyl radicals (·OH), and hydrogen peroxide (H 2 O 2 )) involved in the heterogeneous photocatalytic reactions effectively degrade various ambiguous…”
Section: Introductionmentioning
confidence: 99%